PENGARUH PAD DAN DANA PERIMBANGAN TERHADAP KINERJA KEUANGAN PEMERINTAH DAERAH DI WILAYAH SARBAGITA PROVINSI BALI - Putri, Ni Kadek Novia Indrawati; Darmayanti, Ni Putu Ayu (E-Jurnal Manajemen; Vol 8 No 5 (2019), 2019)
This study aims to determine the effect of local revenue and balancing funds on the financial performance of local governments. This research was conducted in Denpasar City, Badung Regency, Gianyar Regency, and Tabanan Regency or often referred to as the Sarbagita area. The research design in this study used an associative approach. The population and sample in this study were Denpasar City Government, Badung Regency, Gianyar Regency, and Tabanan Regency (Sarbagita region) with the method of determining the sample used was a saturated sampling method. Data collection uses the non-participant observation method by observing the realization report of the District / City Government Budget in the Sarbagita region for the 2012-2016 fiscal year with the analysis technique used is multiple linear regression. The results of the analysis show that local revenue and balance funds have a significant negative effect on the financial performance of local governments. These results indicate that the increasing acquisition of local revenue and receipt of balance funds will be followed by a decrease in the financial performance of regional governments. Keywords : local revenue, balance funds, local government financial performance